Profile adultery ; A Necessary evil? ; Treasures from the earth [videorecording] - Lazaro, Cheche; Ortigas, Marga (Quezon City Probe Productions, 1994)
Discusses the bill seeking to redefined adultery and change the word woman to person in Article 333; Two popular pesticides manufactured by Hoechst Company banned by the Philippine government; and a craftsman named Jon Pettyjohn who creates masterpieces from clay.
Profile : Adultery (20 min.) -- A necessary eviln -- (11 min.) -- Treasures from the earth (11 min.).
VHS.
Reporter, Marga Ortigas.
Keywords: Pettyjohn, Jon; Adultery -- Law and legislation. -- Philippines; Pesticides -- Philippines; Pottery